The Strength Reduction Factors for Seismic-Isolated Bridges Characterized by SDOF Bilinear Systems in Far-Fault Areas - Wu, Y.; Wang, H.; Li, A.; Sha, B.; Bi, Kaiming (Taylor & Francis Ltd., 2017)
This article presents a statistical study on strength reduction factors for seismic-isolated bridges in far-fault areas. 1410 ground motions are selected and modified to be compatible with the recommended response spectra. Then, they are divided into 60 groups to investigate the effects of PGA/PGV ratios, soil conditions and post-to-pre-yield stiffness ratio. Results show that reduction factors are significantly affected by the PGA/PGV ratio, while the latter two items are not as important as the first one. Finally, an improved equation to estimate the reduction factor is proposed, and the accuracy of the equation is verified by additional records.